A tale of two decades: The ECB's monetary policy at 20 - Massimo Rostagno; Carlo Altavilla; Giacomo Carboni; Wolfgang Lemke; Roberto Motto; Arthur Saint Guilhem; Jonathan Yiangou (European Central Bank (ECB), 2019)
The 20th anniversary of Economic and Monetary Union (EMU) offers an opportunity to look back on the ECB's record and learn lessons that can improve the conduct of policy in the future. This paper charts the way the ECB has defined, interpreted and applied its monetary policy framework - its strategy - over the years from its inception, in search of evidence and lessons that can inform those reflections. Our "Tale of Two Decades" is largely a tale of "two regimes": one - stretching slightly beyond the ECB's mid-point - marked by decent growth in real incomes and a distribution of shocks to inflation almost universally to the upside; and the second - starting well into the post-Lehman period - characterised by endemic instability and crisis, with the distribution of shocks eventually switching from inflationary to continuously disinflationary. We show how the most defining element of the ECB's monetary policy framework, its characteristic definition of price stability with a hard 2% ceiling, functioned as a key shock-absorber in the relatively high-inflation years prior to the crisis, but offered a softer defence in the face of the disinflationary forces that hit the euro area in its aftermath. The imperative to halt persistent disinflation in the post-crisis era therefore called for a radical, unprecedented policy response, comprising negative policy rates, enhanced forms of forward guidance, a large asset purchase programme and targeted long-term loans to banks. We study the multidimensional interactions among these four instruments and quantify their impact on inflation and economic activity.
Keywords: E50; E51; E52; 330; monetary policy; financial crises; policy strategy; non-standard measures